Relationship between epicardial adipose tissue and body muscle-to-fat ratio in patients with type 2 diabetes mellitus - Siho Hidayet; Emine Hidayet (Medicine Science, 2020)
Type 2 Diabetes mellitus (T2DM) is shown as an important risk factor for the development of cardiovascular diseases worldwide. Epicardial adipose tissue (EAT) has been associated with cardiovascular diseases. The body muscle-to-fat ratio measured by bioelectric impedance (BIA) is associated with cardiac dysfunction. In this study, we aimed to evaluate the relationship between EAT and body muscle-to-fat ratio in T2DM patients. The 125 consecutive T2DM patients and 46 healty volunteers included in the study. EAT was measured by using transthorasic echocardiograph (TTE). Data were obtained BIA analysis in all patient. The muscle-to-fat ratio measured by BIA and EAT was compared between the two groups. There was a significant difference between the groups in terms of waist circumference (WC), fat mass, fat mass ratio, muscle mass and muscle-to-fat ratio. E (p [Med-Science 2020; 9(2.000): 454-8]